Integrating Building Information Modeling (BIM) and Virtual Reality (VR) for Sustainable Universal Design at the Conceptual Stage of Housing Projects - Rostamiasl, Vafa (Université d'Ottawa | University of Ottawa, 2024)
While Canada is witnessing a significant demographic alteration due to the aging population, particular re-evaluation, and revolutionary methodologies in the designing domains, notably in residential construction, are becoming a necessity. This thesis elucidates the complicated challenges and paradigm shifts in the housing demands, which is caused by this demographic evolution, focusing primarily on the development of a computer model that integrates Universal Design (UD), Building Information Modeling (BIM), Virtual Reality (VR), Energy Analysis (EA), Life Cycle Assessment (LCA), and Life Cycle Cost Analysis (LCCA) to be used when creating homes for optimal aging-in-place. The said model is innovative by utilizing new plug-ins and databases, allowing for the application of UD principles at the conceptual stage in an efficient and cost-effective manner. It enables designers and owners to select the best design options based on their predefined criteria and offers real-time simulation in an interactive environment, improving communication and interaction between owners and designers. This helps in minimizing future modifications by aligning designs more closely with the inhabitants' needs. The model accommodates the incorporation of various universal and accessible design guidelines, fostering the automated retrieval of essential information and components, thereby facilitating designers and homeowners in opting for optimal design and providing an exclusive real-time interactive simulation environment, effective communication and cooperation between designers and owners, and mitigating future architectural modifications by aligning designs closely with the inhabitants' needs. The model has the form of a cloud-based integration between BIM, UD, Aging-in-Place (AIP) prerequisites, and Virtual Reality (VR), which enhances owner engagement early during the initial design stages and optimizes the overall design outputs. Furthermore, it incorporates energy analysis tools through novel plug-ins developed to improve the design of elements such as window design and building orientation, to enable optimized energy consumption, and to enhance the building’s performance toward sustainable universal design (SUD). In addition, the model incorporates a module that is dedicated to Life Cycle Assessment (LCA). That module facilitates the automatic calculation of carbon emissions by enabling designers to select optimal materials for components such as walls and roofs. Incorporating LCA into the model offers a framework for evaluating the environmental impacts of design choices, besides enhancing the sustainability and ecological considerations of aging-in-place residential design. Whereas, LCCA, which is integrated into this automated model, offers a framework to evaluate the economic impacts of incorporating UD principles by assessing the entire life cycle of a building, from conception to renovation or disposal. It elucidates the economic possibility of long-term investments in UD, showcasing substantial cost reductions in future renovations due to upfront incorporations of accessibility features. This research emphasizes the importance of integrating BIM, UD, VR, EA, LCA, and LCCA during the decision-making processes that are related to aging-in-place design, offering a foundational approach for designing homes that improve the quality of life for seniors. This holistic approach underscores the importance of addressing environmental concerns alongside functional and economic considerations in creating homes tailored for optimal aging-in-place experiences. These homes are financially sustainable and support the aging population's desire to live independently and comfortably in their later years, contributing significantly to the development of inclusive and adaptive residences for Canada's aging demographic.
Keywords: Building Informatio Modeling; Virtual Reality; Universal Design; Building Codes; Accessibility; Life Cycle Assessment; Life Cycle Cost Analysis; Energy Analysis; Automation; Digitalization; Aging in Place